The Transformation of The Word: Literary Activities and Works During the Apostolic Period of Prophet Muhammad SAW - Visca Citra Nazia; Myrna Nur Sakinah (Indo Publishing, 2026)
This research explores the sociolinguistic and aesthetic paradigm shift in Arabic literature during the Apostolic period of Prophet Muhammad SAW (7th century CE), marking the transition from Jahiliyyah tribal oral traditions to centralized Islamic monotheism. Utilizing a qualitative descriptive method with a stylistic (uslub) approach, the study deconstructs ten core verses of Hassan bin Thabit’s monumental poem, Burikta Ya Qabra Ar-Rasuli. The primary analytical focus lies on Thabit’s rhetorical sophistication—including alliteration, metaphor, personification, and silepsis—in mediating profound grief over the passing of Prophet Muhammad SAW. Findings indicate that the Apostolic period did not erase past poetic traditions but rather revolutionized their essence and function. Literature was transformed from an instrument of tribal fanaticism (ta’asub) into a medium for social, moral, and political transformation fundamental to state-building in Medina. Furthermore, the Ijaz al-Qur'an served as a linguistic anchor that standardized Classical Arabic (Fusha), providing a new rhetorical framework for poets such as Hassan bin Thabit. This study concludes that the literary transformation of this period laid the eternal foundation for all future global Arabic literary developments .